Analysis of Clinical Dose–Response in Small-Molecule Drug Development: 2009–2014. (3rd April 2017) - Thomas, Neal; Roy, Dooti
ABSTRACT: A meta-analysis of dose–response studies is reported for small-molecule drugs approved by the U.S. Food and Drug Administration (FDA) between January 2009 and May 2014. Summaries of the study designs are presented, including the number of studies conducted for each drug, dosing range, and the number of doses evaluated. Most drugs were studied on a ⩽ 4-fold range. Most of the study designs and their analyses focused on a small number of pairwise comparisons of dose groups to placebo. For the meta-analysis, efficacy endpoints were evaluated at a single landmark time. Safety endpoints were not collected. The commonly used Emax model was fit for each drug. Due to the limited number of doses and dosing ranges, maximum likelihood estimation applied to drugs separately performed poorly. Bayesian hierarchical models were successfully fit producing Emax curves that represented the data well. The distributions of the Emax model parameters were consistent with previously reported distributions estimated from a sponsor-specific meta-analysis of dose response. Assessment of model fit, which focused on potential nonmonotone loss of efficacy at the highest doses, supported the use of the Emax curves. The meta-analysis provides additional empirical basis for Bayesian prior distributions for model parameters. Supplementary materials for this article are available online.